2011
DOI: 10.1007/s10560-011-0247-8
|View full text |Cite
|
Sign up to set email alerts
|

Placement Instability and Risky Behaviors of Youth Aging Out of Foster Care

Abstract: Youth who age out of foster care are at risk of poor outcomes and risky behaviors in young adulthood. Yet, little is known about what child welfare workers can do to decrease these risks. The effect of foster care placement instability on substance use and risky sexual behaviors is examined using data from 114 young adults who aged out of care. When controlling for variables commonly associated with these behaviors, a history of foster care placement instability increased the young adults' likelihood to use su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(51 citation statements)
references
References 45 publications
3
44
0
3
Order By: Relevance
“…Many other young adults, not from foster care, have the continued support of their parents into adulthood (Clark, 2007;Statistics Canada, 2007). Research has identified that former youth in-care have a higher likelihood, compared to their peers, of: incarceration, substance abuse, homelessness, mental illness, and not completing high school (Drowsky & Courtney, 2009;Freundlich & Avery, 2006;Landvoy, 2009;Stott, 2012;Tweddle, 2005).…”
Section: Avismentioning
confidence: 99%
See 4 more Smart Citations
“…Many other young adults, not from foster care, have the continued support of their parents into adulthood (Clark, 2007;Statistics Canada, 2007). Research has identified that former youth in-care have a higher likelihood, compared to their peers, of: incarceration, substance abuse, homelessness, mental illness, and not completing high school (Drowsky & Courtney, 2009;Freundlich & Avery, 2006;Landvoy, 2009;Stott, 2012;Tweddle, 2005).…”
Section: Avismentioning
confidence: 99%
“…In some cases, a feeling of powerlessness is almost inevitable, given the numerous decisions made for them (Samuels, 2008;Schofield & Beck, 2009;Stott, 2012). In child protection cases, children sometimes have no choice regarding their removal from family, community, and school.…”
Section: Supports Control and Stabilitymentioning
confidence: 99%
See 3 more Smart Citations